2009
DOI: 10.1089/tmj.2008.0068
|View full text |Cite
|
Sign up to set email alerts
|

Telemedicine for Post-Myocardial Infarction Patients: An Observational Study

Abstract: "SHL" Telemedicine (established 1987 in Israel) provides professional care to subscribers who use cardiobeepers and contact its medical call center via telecommunication networks. The extended 6-month Acute Coronary Syndrome Israel Survey (ACSIS) 2004 involved all 26 intensive cardiac care units in Israeli hospitals. We compared the 1-year survival rates of the "SHL" Telemedicine subscribers and ACSIS participants who survived hospitalization after sustaining an acute myocardial infarction. The myocardial infa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 43 publications
0
10
1
1
Order By: Relevance
“…Anyway, it should be observed that the study of Ortolani et al 33 reported in-hospital mortality for all causes and not only mortality due to myocardial infarction. On the other hand, Waldmann et al 30 and Roth et al 32 provided data on 12-month survival; in particular, …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anyway, it should be observed that the study of Ortolani et al 33 reported in-hospital mortality for all causes and not only mortality due to myocardial infarction. On the other hand, Waldmann et al 30 and Roth et al 32 provided data on 12-month survival; in particular, …”
Section: Discussionmentioning
confidence: 99%
“…All patients had CAD: three study groups 29,31,33 had AMI, and two 30,32 had established CAD and were followed up in order to assess the 12-month combined end point (mortality, morbidity, and rehospitalization) 30 or survival. 32 Most end points were represented by the time elapsed from the occurrence of the cardiac event to the medical intervention; in particular, ''door to balloon'' time was the time lag from hospital admission to the first inflation of the balloon used for the angioplasty, ''onset to door'' time was defined from the onset of symptoms to the hospital admission, ''door to lysis'' time was from the hospital admission to the beginning of thrombolysis, ''onset to lysis'' time was from the onset of symptoms to the thrombolysis, and ''onset to balloon'' time was from the onset of symptoms to the first inflation of the balloon. Mortality was investigated in all studies: the percentage of patients who died was always higher in the control group than in the intervention group, and mortality was more than doubled in the studies of Waldmann et al, 30 Roth et al, 32 and Ortolani et al 33 …”
Section: Data Extractionmentioning
confidence: 99%
“…When two models of assistance (telecardiology versus usual care) for patients discharged after acute coronary syndrome were compared in the assessment of angina, telecardiology slightly reduced hospital readmissions (44% versus 56%) [37]. In a large population who survived hospitalization after sustaining an acute myocardial infarction, subjects followed by telemedicine support had significantly higher survival rates at 1 year [38]. The direct 12-week comparison of a conventional and a telemedicine approach showed the suitability of telemedicine for delivering cardiac rehabilitation for risk factor modification and exercise monitoring to patients who otherwise would not have access to it [39].…”
Section: Telemedicine For Rehabilitation and Chronic Heart Failurementioning
confidence: 99%
“…It is behind the scope of this article to describe the tremendous progress made in the field of telemedicine in both the diagnosis and treatment of atrial and ventricular arrhythmic events [8,9,19], early diagnosis of acute myocardial infarction [6], treatment and follow-up of patients suffering from heart failure [20,21] and post-myocardial [22] follow-up. These applications also substantially decreased emergency department visits and hospitalizations, prolonged survival, and led to impressive cost savings [23,24].…”
Section: Discussionmentioning
confidence: 99%